Pandemic Considerations on Essential Oral Health Care. (March 2021) - Benzian, H.; Beltrán-Aguilar, E.; Mathur, M.R.; Niederman, R.
The coronavirus disease 2019 (COVID-19) pandemic revealed a lack of consensus on the concept of essential oral health care. We propose a definition of essential oral health care that includes urgent and basic oral health care to initiate a broader debate and stakeholder alignment. We argue that oral health care must be part of essential health care provided by any health system. Essential oral health care covers the most prevalent oral health problems through an agreed-on set of safe, quality, and cost-effective interventions at the individual and community level to promote and protect oral health, as well as prevent and treat common oral diseases, including appropriate rehabilitative services, thereby maintaining health, productivity, and quality of life. By default, essential oral health care does not include the full spectrum of possible interventions that contemporary dentistry can provide. On the basis of this definition, we conceptualize a layered model of essential oral health care that integrates urgent and basic oral health care, as well as advanced/specialist oral health care. Finally, we present 3 key reflections on the essentiality of oral health care. First, oral health care must be an integral component of a health care system's essential services, and by implication, oral health care personnel are part of the essential health care workforce. Second, not all dental care is essential oral health care, and not all essential care is also urgent, particularly under the specific risk conditions of the pandemic. Third, there is a need for criteria, evidence, and consensus-building processes to define which dental interventions are to be included in which category of essential oral health care. All stakeholders, including the research, academic, and clinical communities, as well as professional organizations and civil society, need to tackle this aspect in a concerted effort. Such consensus will be crucial for dentistry in view of the Sustainable Development Goal's push for universal health coverage, which must cover essential oral health care.